Instrumentarium wieloletniego programowania rozwoju jednostki samorządu terytorialnego - Dylewski, Marek (Tools of long-term planning of development in local governments, 2006)
The article presents possibilities of using instruments for planning and programming processes of development in local governments. Long-term investment program, a forecast of public debt, long-term financial plan and strategy of local government development can be the main tools in the long-term programming. However, effective use of the tools is determined by a complex approach that still doesn’t exist in our environment.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1129, s. 105-113